Industrialization And Work Values In Kedah, Penang And Great Britain: A Study From The Convergence-Divergence-Crossvergence Perspective - Yap, Chee Yeong (2021)
The lack of discovery of the influence of industrialization on work values in Malaysian societies deters the further understanding of the reaction of Malaysians’ values to macro-level social changes. The review of prior studies shows that the influence of industrialization on work values is not consistent across societies, suggesting that it depends on the kind of society. This study aims to determine the Convergence-Divergence-Divergence (CDC) condition of work values in Malaysian societies to learn more about the influence of industrialization on Malaysians’ work values and the reaction of Malaysians’ values to macro-level social changes. In this context, work values are conceptualized into four dimensions: extrinsic work orientation, intrinsic work orientation, work centrality, and work-life balance. To test the convergence, divergence, and crossvergence hypotheses, the CDC framework was employed. 532 respondents from three regions with different extents of industrialization were involved. 175 Kedah respondents and 177 Penang respondents were recruited using convenience sampling through a face-to-face survey and an online survey, while 180 Great Britain respondents were obtained from secondary data. The responses were analyzed using the Mann-Whitney U Test and Kruskal-Wallis H Test. The results support the crossvergence hypothesis. Two out of four dimensions of work values in Penang do not differ significantly from that in Kedah and three out of four dimensions of work values in Penang do not differ significantly from that in Great Britain. This study suggests a verdict of crossvergence in work values in Malaysian societies. The extent of industrialization is influential on some dimensions of work values while some are not influenced. This implies that Malaysian societies are somewhere in the middle between adaptive and resistant when dealing with macro-level social changes.